(The Social and Political life of President John Quincy Adams after the End of his Presidency of the United States of America 1828-1848) (Journal of the College of Basic Education, 2022)
The Research Reviews a major Episode of the life of the Sixth President of the United States of America, President John Quincy Adams, Specifically his life after losing the Elections of 1828, as it dealt with his Social life, his Political life, and finally his struggle with illness, which led to his death in 1848, and in the folds of the Study we dealt with the Role of President John Quincy Adams in pursuing the problem of slavery, as well as his role in the sessions of the US Federal House of Representatives (Congress), Representing Massachusetts, and his defense of the rights of his people, In addition, the Research will be Under the Title of (The Social and Political life of President John Quincy Adams after the End of his presidency of the United States of America 1828-1848).